Model Pendekatan Big Five Personality untuk Mereduksi Burnout dalam Meningkatkan Kinerja Karyawan - Muhammad Darari Bariqi; Mochammad Isa Anshori (Management and Education Journal, 2023)
Burnout is a state of chronic psychological stress. This can cause individuals to experience emotional exhaustion and low motivation to work. Burnout is a term that describes the emotional state of a person who feels tired and bored, emotionally, physically, mentally, depersonalized and has decreased personal achievement as a result of increased work demands. Personality is one of the factors that can cause burnout. In this study, the personality used is the big five personality approach which refers to the five factors of human personality. The objective of this study is to find out how the big five personality approach reduces burnout to improve the performance of the employees of PT. BRIsyariah Bank KCP Bangkalan Trunojoyo. This study is a qualitative descriptive type of research. In this study, the data obtained are data from participant observation, in-depth interviews and documentation conducted on four selected informants who are taken using purposive sampling and snowball sampling. The findings in this study reveal that the big five personality approach can reduce burnout because the individuals in this study have positive personalities in the five dimensions of the big five personality which can automatically improve performance.